To peck or not to peck: the influence of early-life social environment on response inhibition and impulsive aggression in Japanese quails - Alizée Vernouillet; Kathryn Willcox; Reinoud Allaert; Anneleen Dewulf; Wen Zhang; Camille A. Troisi; Sophia Knoch; A. Martel; Luc Lens; Frederick Verbruggen (Royal Society Open Science)
Deficits in response inhibition (RI; i.e. the ability to suppress inappropriate responses) may contribute to increased impulsive aggression (IA; i.e. unplanned behaviours that harm others). Since early-life environment might influence the development of RI, it could also indirectly affect IA. However, this relationship has rarely been directly examined. Here, we investigated whether RI is associated with IA and whether this relationship explains the effects of early-life social environments on IA in juvenile Japanese quails (Coturnix japonica). Quails (n = 120) were raised in two social conditions: small groups of five birds or large groups of 15 birds. Response inhibition was assessed using the barrier and cylinder tasks, while IA was measured in two contexts—within a group of five familiar individuals and in a dyad with an unfamiliar individual. We found that some aspects of RI were related to IA. Furthermore, quails reared in small groups showed significantly poorer RI than those reared in large groups. Yet, IA did not significantly differ between the two conditions. These findings suggest that, while IA is partly related to RI, other factors mitigate the effects of early social environments on its expression.